Psychometric Properties of the Portuguese Version of The PERMA-Profiler - Alves, Marcela Almeida (2023)
This study evaluates the psychometric properties of a Portuguese version of The PERMA Profiler in a sample of 1258 Portuguese adults (72.3% females) with a mean age of 36.74 years (SD = 11.313). The PERMA Profiler is a questionnaire that assesses the five dimensions of psychological flourishing, according to Seligman’s well-being theory. According to this theory, the well-being pillars known by the acronym PERMA are positive emotions, engagement, relationships, meaning, and accomplishment. Confirmatory factor analysis was conducted to test Seligman’s model. Results support a reasonable model fit for the five-factor model, but based on the results of bootstrap sample analysis the model was not confirmed. There is also a lack of discriminant validity between PERMA constructs and a lack of validity and reliability of engagement factor. Internal consistency was satisfactory for all five sub-scales, except for engagement. Concurrent validity was demonstrated through the strong and very strong correlations between the PERMA factors and Flourishing Scale. A Portuguese version of The PERMA Profiler is a new tool to assist researchers to refine the measurement and understanding of well-being in Portuguese cultures. Future recommendations and limitations are highlighted.